New species of Ophryosporus (Eupatorieae Asteraceae) from Peru - Sagástegui Alva, Abundio (2008)
Ophryosporus marchii Sagást. & E. Rodr. is described as a new species of Ophryosporus Meyen (Eupatorieae: Asteraceae) from the Department of Cajamarca, Peru. This new species is apparently endemic to the province of Contumaza and closest relative to O. sagasteguii H. Rob. It is critically compared with this species and data on its geographical distribution, ecology and conservation status are provided.